2022
DOI: 10.52922/ti78610
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and trauma among young people in the youth justice system

Abstract: This study examines the prevalence of adverse childhood experiences (ACEs) in a representative sample of young people under youth justice supervision in South Australia. The analysis showed that not only was the prevalence of ACEs particularly high in this population (89% experienced a combination of maltreatment and household dysfunction), but so too were trauma symptomatology, substance use, and internalising and externalising behaviours (with more than two-thirds of young people scoring in the clinical rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The prevalence of adversity and trauma among justice-involved young people in South Australia was examined in more detail by Malvaso et al (2022). In a representative sample of 184 young people under Youth Justice supervision, almost 90% self-reported exposure to multiple forms of adversity in childhood.…”
Section: Co-producing Trauma-informed Youth Justice In Australia?mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of adversity and trauma among justice-involved young people in South Australia was examined in more detail by Malvaso et al (2022). In a representative sample of 184 young people under Youth Justice supervision, almost 90% self-reported exposure to multiple forms of adversity in childhood.…”
Section: Co-producing Trauma-informed Youth Justice In Australia?mentioning
confidence: 99%
“…The prevalence of each type of adversity, which included experiences relating to maltreatment (physical, sexual and emotional abuse, neglect) and household adversity (parental mental illness, incarceration, substance use, death, family and neighbourhood violence and bullying), was up to four times higher than prevalence estimates reported in the international literature (Malvaso et al , 2021 for a review of adverse childhood experiences in justice-involved populations). Exposure to maltreatment and adversity was found to be associated with current trauma symptomatology (with almost 90% of young people scoring in the symptomatic ranges of at least one trauma symptom scale), as well as internalising and externalising behaviours, including substance use (Malvaso et al , 2022). Studies in other Australian jurisdictions also confirm the high prevalence of exposure to adverse, potentially traumatic events and child protection contact commonly experienced by justice-involved young people (Baidawi and Sheehan, 2019; Harris et al , 2022; McGrath et al , 2020).…”
Section: Co-producing Trauma-informed Youth Justice In Australia?mentioning
confidence: 99%
See 1 more Smart Citation
“…Australian First Nations young people are more than 18 times more likely than their non-First Nations peers to be incarcerated (AIHW, 2018). Australian First Nations young people in a South Australian (SA) study were found to be incarcerated younger, more often for violence related offences and to experience poorer mental health (Malvaso et al , 2022). In NSW, analysis of the experiences of 1,055 young people involved with justice due to DV assault offences found that 21% of the young people were First Nations, more than 90% had some type of ADVO applied against them, while just under 20% of young people charged with DV assault had been bail refused at the time of their incident (NSW Government Department of Communities and Justice, 2022).…”
Section: Purposementioning
confidence: 99%
“…A one-size-fits-all approach to work with justice-involved young people that does not acknowledge the role of trauma and cultural responsiveness is likely to be ineffective. Co-production and co-design with young people can enhance access, equity and participation in interventions (Malvaso et al , 2022).…”
Section: Purposementioning
confidence: 99%